PERBANDINGAN KADAR PEREKAT TAPIOKA DENGAN ARANG DARI CANGKANG BUAH KARET TERHADAP BRIKET ARANG - Ahmad Reza; Akhyar Ali; Raswen Efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The rubber shell contain beneficial compounds lignin and cellulose which is quite high and has not been utilized optimally. Therefore, this study aims to take advantage of rubber shell as the main material for the manufacturing of charcoal briquettes and charcoal briquettes obtain formulations are of good quality. This study was conducted experimentally using Complete Random Design (CRD) with 4 treatments and 4 replications and continued with Duncan’s New Multiple Range Test (DNMRT) at 5% level. Treatments at this research were P1 (adhesive 3%), P2 (adhesive 5%), P3 (adhesive 7%), P4 (adhesive 9%). Results of the analysis of variance indicate that the ratio of adhesive has a significant effect on water content, ash content, density, volatile content, carbon content, and calorific value. The best formulation was obtained from 5% adhesive that had 5.52% water content, ash content 15.47%, 0.46 g/cm3 density, 13.47 vapour content, 65.52 tied carbon, and heating value 5.153.03 cal/g. Keywords : charcoal, rubber shell, charcoal briquttes